Marketing Practices and Problems of Cotton Cultivators in Virudhunagar District - Balasubramanian, M.; Eswaran, R. (Indian Journal of Marketing, 2008)
Agricultural marketing involves in its simplest form-buying and selling of agricultural products. In modern marketing, the agricultural produce has to undergo a series of transfers or exchanges from one hand to another before it finally reaches the consumer. To sustain the pace of growth adequate marketing infrastructure, conductive policy environment and relevant mechanism for articulating the technological need of producers and processors needs to be organized. The present study is very helpful to know the marketing condition of cotton in Virudhunagar district. This study includes the problems faced by the cotton cultivators and hence it is very creditable to know the marketing structure of cotton.